2004
DOI: 10.1093/mutage/geh018
|View full text |Cite
|
Sign up to set email alerts
|

In vivo kinetics of micronuclei induction by bifunctional alkylating antineoplastics

Abstract: The aim of the present study was to determine in vivo the kinetics of micronucleated polychromatic erythrocyte (MN-PCE) induction in mice, as an approach for studying the mechanism of micronuclei induction by mitomycin C, cis-diamine dichloroplatinum, busulfan and bis-chloroethylnitrosourea, bifuctional alkylating antineoplastic agents having different patterns of crosslink induction. The kinetics of MN-PCE induction was established by scoring the frequency of MN-PCE in 2000 PCE in peripheral blood, for period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 25 publications
6
17
0
5
Order By: Relevance
“…Our previous studies revealed atypical busulfan-dosedependent effects [Morales-Ramírez et al, 2004, 2006. Kinetic studies on the induction of micronuclei in murine peripheral blood erythrocytes indicate that exposure to a low dose of busulfan causes a maximal induction at 32 hr after exposure, and higher doses cause a maximal micronuclei induction at 48 hr after exposure; in addition, the micronuclei induction rate per dose is more than double for the higher dose (Fig.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Our previous studies revealed atypical busulfan-dosedependent effects [Morales-Ramírez et al, 2004, 2006. Kinetic studies on the induction of micronuclei in murine peripheral blood erythrocytes indicate that exposure to a low dose of busulfan causes a maximal induction at 32 hr after exposure, and higher doses cause a maximal micronuclei induction at 48 hr after exposure; in addition, the micronuclei induction rate per dose is more than double for the higher dose (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…The low (30 lmol/kg bw) and high (80 lmol/kg bw) doses of busulfan were selected from our previous in vivo studies in mice using micronuclei and single cell gel assays [Morales-Ramírez et al, 2004, 2006. These doses caused a differential response with both end points as can be seen in Figure 3.…”
Section: Busulfan Dosementioning
confidence: 99%
See 2 more Smart Citations
“…A droga TMZ é um agente alquilante que atua pela metilação das bases do DNA, sendo a lesão mais frequente, mutagênica e responsável pela indução da morte celular a metilação da MORALES-RAMIREZ et al, 2004).…”
Section: Investigação Da Participação De Ner E Tls Na Citotoxicidade unclassified